When the moon set over Haifa - Allen, Angelina Diliberto (Wilmette, Illinois Bahá'í Publishing, 2021)
"On November 28, 1921, the head of the Bahá'í Faith, 'Abdu'l-Bahá, passed away. For Bahá'ís, 'Abdu'l-Bahá was more than the leader of their religion. Shoghi Effendi wrote that 'Abdu'l-Bahá was "the Moon of the Central Orb of this most holy Dispensation" (Shoghi Effendi, The World Order of Bahá'u'lláh, p. 134). The night of 'Abdu'l-Bahá's ascension was a night of the waning moon, which illustrates the profound darkness that was felt by those who were present at the time of the passing of 'Abdu'l-Bahá. The darkness would be only temporary, for the passing of 'Abdu'l-Bahá marked the dramatic opening of the Formative Age, a period in the history of humanity that will witness the unfoldment of a religious cycle that will last half a million years (Shoghi Effendi, The World Order of Bahá'u'lláh, pp. 101-102). There were six Western believers in Haifa on the night of the ascension of 'Abdu'l-Bahá: Mr. John Bosch and Mrs. Louise Stapfer Bosch from Geyserville, California; Dr. Florian Krug and Mrs. Grace Krug from New York, and Fraulein Johanna Hauff from Stuttgart. All of them were there as pilgrims. The only other Western believer present in Haifa was Mr. Curtis Kelsey from New York, who was in Haifa to install electrical power plants to light the shrines of the Báb and Bahá'u'lláh. This book tells the story of these believers, how they became Bahá'ís, the circumstances that led them to Haifa, and how their experience at the time of the ascension of 'Abdu'l-Bahá shaped their path of service to the Cause of God. The intent is to give the reader the feeling of being in the holy land, one hundred years ago, when the moon of 'Abdu'l-Bahá set over Haifa"--
Includes bibliographical references
Keywords: ʻAbduʼl-Bahá -- 1844-1921 -- Death and burial; Bahais -- Biography